ZYG11A Is Expressed in Epithelial Ovarian Cancer and Correlates With Low Grade Disease - Achlaug, Laris; Somri-Gannam, Lina; Meisel-Sharon, Shilhav; Sarfstein, Rive; Dixit, Manisha; Yakar, Shoshana; Hallak, Mordechai; Laron, Zvi; Werner, Haim; Bruchim, Ilan (Frontiers in Endocrinology, 2021)
The insulin-like growth factors (IGF) are important players in the development of gynecological malignancies, including epithelial ovarian cancer (EOC). The identification of biomarkers that can help in the diagnosis and scoring of EOC patients is of fundamental importance in clinical oncology. We have recently identified the ZYG11A gene as a new candidate target of IGF1 action. The aim of the present study was to evaluate the expression of ZYG11A in EOC patients and to correlate its pattern of expression with histological grade and pathological stage. Furthermore, and in view of previous analyses showing an interplay between ZYG11A, p53 and the IGF1 receptor (IGF1R), we assessed a potential coordinated expression of these proteins in EOC. In addition, zyg11a expression was assessed in ovaries and uteri of growth hormone receptor (GHR) knock-out mice. Tissue microarray analysis was conducted on 36 patients with EOC and expression of ZYG11A, IGF1R and p53 was assessed by immunohistochemistry. Expression levels were correlated with clinical parameters. qPCR was employed to assess zyg11a mRNA levels in mice tissues. Our analyses provide evidence of reduced ZYG11A expression in high grade tumors, consistent with a putative tumor suppressor role. An inverse correlation between ZYG11A and p53 levels in individual tumors was noticed, suggesting a functional interaction between these genes with potential relevance in cancer biology. Data is consistent with a putative tumor suppressor role of ZYG11A and justifies further exploration of the role of ZYG11A as a novel biomarker in EOC.